AN ANNOTATED TRANSLATION OF SIREN’S SONG - Widowati, Risca (Universitas Gunadarma, 2017)
This is an annotated translation research. The purposes of this research are: (1) to find out what the problems are in translating the novel entitled “Siren’s Song” into Indonesian and (2) to find out what the solutions are to the problems. This research used an introspective and a retrospective method. There are 25 data analyzed which depicted difficulties encountered in translating a text in this research. The result showed that in translating a text the present translator/ the researcher is not applying all of the principles of translation advocated by Allan Duff and all of the strategies of translation advocated by Chesterman. To solve all problems that encountered in translating a text in this research, the researcher as a translator only uses 5 principles from 13 principles of translation namely, idiom (2 data), meaning (15 data), style and clarity (4 data), register (2 data) and source language influence meaning (2 data), and 16 strategies of translation namely, paraphrase (2 data), synonym (2 data), c ohesion change (2 data), clause structure change (2 data), transposition (2 data), loan (2 data), cultural filtering (2 data), antonym (2 data), scheme change (2 data), phrase structure change (1 data), unit shift (2 data), calque (1 data), interpersonal change (1 data) and explicitness change (2 data). Besides, the related theories advocated by Larson, Baker, Nida & Taber, Newmark, Bassnett, Vinay and Darbelnet, Alwi, and Munday, are really helping in solving all problems encountered. From the research result, the researcher/translator recommends other researcher who are interested in the same topic, annotated translation, to use Indonesian source text to be translated into English target text in natural translation and also to collect more data in order to makea more ellaborate analysis.Keywords: Annotated, introspective, retrospective, novel.